When anger and happiness generate concessions: investigating counterpart's culture and negotiation intentions. Issue 1 (19th September 2021) - Ramirez-Marin, Jimena Y.; Barragan Diaz, Adrian; Guzman, Felipe A.
Abstract : Purpose: Drawing from the emotions as social information theory, this paper aims to investigate the differential effects of emotions in inter vs intracultural negotiations. Design/methodology/approach: The authors used one face-to-face negotiation and two experimental scenario studies to investigate the influence of emotions (anger vs happiness) and negotiation type (intercultural vs intracultural) on concession behavior. Findings: Across the three studies, the results consistently show that angry opponents from a different national culture obtain larger concessions from negotiators. A face-to-face negotiation shows that happy opponents from the same culture are able to obtain larger concessions from negotiators. Additionally, the negotiator's intentions to compromise and yield mediate the relationship between the interaction of emotions and counterpart's culture on concessions. Research limitations/implications: Two limitations are that the studies were conducted in a single country and that they use different types of role-playing designs. The empirical implications provide evidence of the moderating effect of the counterpart's culture on the effect of anger on concessions. Then, providing two different mechanisms for concessions. Practical implications: The research helps global negotiators who face counterparts from different nationalities. It suggests that these negotiators should be mindful of their counterpart's emotions in intercultural negotiation as anger seems to generate more concessions in this setting. Originality/value: The article is among the first studies to show that the combination of the counterpart's culture and emotions has an effect on concessions in negotiation. Compromising and yielding are mediating mechanisms for this moderated effect. As opposed to previous studies that use one type of research design, the research combines face-to-face and scenario methodologies to test the predictions.